Dentro e fora de si: modos de ser/estar jovem na escola - Meireles, Marta Martins (2016)
This research investigated how the ways of being young to configure and reconfigure the school-context. In this sense, from the qualitative approach, in dialogue with the methodolog-ical perspective of meanings Network and Cartographic Research, sought to capture speeches, expressions and youth practices that are established in the young-school interaction, consider-ing contextual, subjective and specific aspects the reality investigated. The Production of the data was outlining in a fabric characterized procedurally in a mesh composed of nature, of semiotic elements - contexts, interactions and discursive practices through unsystematic ob-servations in a public school, with records in field diary and discussion groups, which told with the participation of eight young people from the institution. Also, I used the photographs production to subsidize the construction of narratives about what was experienced. This me-thodological approach was used at times as a strategy to promote the conversation with young people, and at the end, as a perspective to present data, from three scenes: sociability among young people; expressions of youth protagonism and be young, being a student. Young people have shown that sociability, that is, the relationship with peers, take on different dimensions: affective, reflective and formative. The encounter with the other and the conversations in the school environment, respond to different demands: help in coping of the dilemmas and chal-lenges; possible moves beyond itself; promote the place of dialogue / understanding and lead to the recognition of self and other. Survey participants revealed the potential of the expres-sions of youth protagonism at school through participation in collective bodies, dialogue and discursive participation as a form of resistance to silencing political and verticalized power relations that are established at school. Thus, these young people take discursive, political, aesthetic and educational places, reconfiguring the school logic and constituting sometimes positions and practices not provided institutionally. The conditions of being a student and be-ing young, to being configured in ambivalent contexts, demarcate the relationship between young people and the school context as a space marked by tensions, limits, strengths and pos-sibilities. Young people transiting the striated and smooth space, and thus, now undergoing, sometimes negotiating, sometimes escape, giving new meaning and reconfiguring the context of which they are part. So is the resistance, the (non) participation, the desire and the need to build other spaces of sociability/training beyond the classroom and the student condition, young people insist and print at school, although the edges and escapes, brands and youthful expressions.